The relationship of depression and malnutrition with healthy eating index in elderly individuals - Hacer Alatas; Nurgul Arslan; Ozgur Aytas (Medicine Science, 2023)
Depression, malnutrition, and the healthy eating index were assessed in this study of people aged 65 and up who sought treatment at an outpatient clinic for internal medicine. Participants were elderly people from Malatya, Turkiye, who had applied to the outpatient clinic for internal medicine. The three-day dietary recall method was used to obtain the records of food consumption among the elderly. The calculation of Healthy Eating Index-2015 (HEI-2015) scores from food consumption. Geriatric Depression Scale (GDS) was used to define probable depression, and Mini Nutrition Questionnaire-Short Form (MNA-SF) was used to determine nutritional status, using face-to-face interviews. The study were 185 individuals included. The mean age of individuals was 72.19±6.92 years. According to MNA-SF results, 32.3% of women and 27.4% of men were found to be malnourished. The mean body mass ındex (BMI) value of the individuals was 25.73±2.85 kg/cm2, and the BMI value of 56.22% of the individuals was within the normal range. The depression score mean was 8.86±4.73. Depression scores are higher in women, those with low monthly education and income, those who use multiple drugs, those with a low HEI-2015 score, and those who use them. There is a relationship between depression score and eating score. As the nutrition score and the HEI-2015 score decrease, the depression score increases. This study indicates that depressed older people consume less food. Early detection of depression and malnutrition is beneficial. Older adults should routinely use brief, easy-to-obtain diagnostic tools such as the MNA and GDS questionnaires to treat these related health issues quickly and effectively. [Med-Science 2023; 12(3.000): 922-8]